The mud traditional architecture of the Sudan and Saudi Arabia: The difference in employment techniques - Ibrahim, Ahmed Osman (Eximia, 2022)
Mud is made of mixing water and any combination of soil, silt, and clay. Soil to be used for mud should be devoid of organic matter. When water is mixed with soil it forms mud, which is the preferable combination necessarily used as a building material. As a building material mud has two main forms; cob and adobe or sun dried bricks, which are of much concern in this research. In this research, just the term “Mud” will be used referring to the “soil mud”. There are many forms of mud as a building material as; earth bricks, soil bricks, adobe, sun dried bricks, clay brick, stabilized bricks, rammed earth or cob. The method adopted in coming out with this research is analytical in which a comparison between the method of employing mud as an architectural building material in the Sudan and Saudi Arabia emphasizing the difference in need in the two countries. This research investigate whether there are any differences in the techniques and methods of employing mud in all construction stages from the stage of bringing the most suitable soil used in making bricks until the stage of its employment as plastering and decorative material.